2018
DOI: 10.3390/rs10111769
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Effects on Snow Accumulation: Observations from Lidar, Canonical-View Photos, and Continuous Ground Measurements from Sensor Networks

Abstract: A variety of canopy metrics were extracted from the snow-off airborne light detection and ranging (lidar) measurements over three study areas in the central and southern Sierra Nevada. Two of the sites, Providence and Wolverton, had wireless snow-depth sensors since 2008, with the third site, Pinecrest having sensors since 2014. At Wolverton and Pinecrest, images were captured and the sky-view factors were derived from hemispherical-view photos. We found the variation of snow accumulation across the landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Mazzotti and colleagues [30] utilized ALS to extract a spatially continuous canopy metric (distance to canopy edge), finding that it performed better than CC for a continental snow environment and could be aggregated to the watershed scale. Zheng et al [31] found that canopy metrics extracted from ALS (e.g., mean canopy height, canopy cover fractions, etc.) explained approximately 50% of the variability of snow accumulation on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Mazzotti and colleagues [30] utilized ALS to extract a spatially continuous canopy metric (distance to canopy edge), finding that it performed better than CC for a continental snow environment and could be aggregated to the watershed scale. Zheng et al [31] found that canopy metrics extracted from ALS (e.g., mean canopy height, canopy cover fractions, etc.) explained approximately 50% of the variability of snow accumulation on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…NASA's Airborne Snow Observatory), their point density is too low for the under-canopy analysis we did here. We have smaller lidar data sets from other areas and dates, but they are much more restricted in elevation and canopy variables, limiting our ability for the space-time substitution in this 2010 data set (Zheng et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, one notices, for instance, a range of wireless sensor networks deployed for habitat and environment monitoring applications; see, e.g., the review paper (Ruiz-Garcia et al 2009) on the use of smart and low-cost sensors in agriculture, food, and related applications. Zheng et al (2018) along with moving sprinkling system for continuous monitoring of crop canopy temperature. Zhou et al (2017) put forward a scalable field cost-effective IoTpowered phenotyping platform, referred CropQuant, for crop monitoring and trait measurement in a way to predict vegetation growth.…”
Section: Soil Pressure and Vegetation Heightmentioning
confidence: 99%